Kontribusi Bentuk Penampang Tiang Terhadap Beban Maximum yang Diterima Pondasi untuk Perencanaan Pondasi pada Tanah Lempung dengan Data CPT Surabaya - Isnaniati Isnaniati (AGREGAT, 2017)
Surabaya city is generally dominated by clay soil. This type of soil has several problems such as low coefficient of permeability, large settlement, and low bearing capacity. Pile foundation is common foundation type applied in clay soil which bedrock layer is relatively deep enough from ground surface. Moreover, pile foundation also has various shapes of cross section which can be appiled in field. The maximum load applied to foundation should be taken into account in order the maximum load (Qmax) does not exceed the allowable bearing capacity of soil (Qallowable).By comparing the cross sections of pile foundation including circle, square, and hexagon, the behaviour of maximum load applied to foundation (Qmax) is investigated based on the results of CPT (Cone Penetrasi Test) using “Philliponnat” method with variations of diameter are 0,3; 0,4; 0,5m at the test locations of (S1, S2 & S3) in order to obtain Qmax < Qallowable.The result of this study indicates that maximum load (Qmax) at the locations of S1, S2 & S3, sorted from the greatest to smallest, are obtained by the cross section shapes of squre, circle, and hexagon. Thereunto, the persentage of maximum load (% Qmax) to the cross section of square at S1 are 100% for square, 79.84% for circle, and 72.01% for hexagon. In addition, at S2 are 100% for square, 74% for circle, and 70,28% for hexagon. The % Qmax at S3 are 100% for square, 95,19% for circle, and 78,82% for hexagon.